Recent advances in photocatalytic HER based on zirconium-containing MOFs over the past three years - Tianxin Zhang; Hao Zhang; Feifan Lang; Enai Dai; Zhen Fan; Houping Xia; Qian Ma; Jiandong Pang (Applied Catalysis O: Open)
The continuous reliance on non-renewable energy sources presents a significant challenge to sustainable development. The photocatalytic decomposition of water for hydrogen production offers a viable solution to this dilemma. Metal-organic frameworks (MOFs) have emerged as one of the most promising materials in the field of photocatalysis due to their controllable structural assembly and extensive modifiability. The advancement of zirconium-based MOFs (Zr-MOFs), renowned for their exceptional chemical stability, has also been rapid. Key priorities in this field include inheriting the high stability characteristic of Zr-MOFs and designing an optimal pore environment while constructing the catalytic active sites. This review lies in conducting a detailed review of the progress of Zr-MOFs in the field of pHER over the past three years from multiple perspectives such as ligands, metal nodes, and pore environment, which is highly targeted and timely. It aims to disseminate relevant findings promptly among researchers and foster further advancements in this field.